2023
DOI: 10.1523/eneuro.0300-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Timelines for Adaptations of Prefrontal Parvalbumin Neurons in Response to Stress and Changes in Anxiety- and Depressive-Like Behaviors

Abstract: Women are twice as likely as men to experience emotional dysregulation after stress, resulting in substantially higher psychopathology for equivalent lifetime stress exposure, yet mechanisms underlying this vulnerability remain unknown. Studies suggest changes in medial prefrontal cortex (mPFC) activity as a potential contributor. Whether maladaptive changes in inhibitory interneurons participate in this process, and whether adaptations in response to stress differ between men and women, producing sex-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Additionally, vmPFC grey matter and functional activity are frequently altered in depression and other stress‐related disorders that disproportionately burden females (Drevets et al., 2008; Riecher‐Rössler, 2017). Accordingly, rodent studies have examined the vmPFC to identify neural substrates contributing to sex‐specific vulnerability (Hurley & Carelli, 2020; van der Zee et al., 2022; Woodward et al., 2023). In vivo monitoring of vmPFC projection neurons also revealed that sex and stress history interact to shape neural activity in response to both appetitive and aversive stimuli (Wallace & Myers, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, vmPFC grey matter and functional activity are frequently altered in depression and other stress‐related disorders that disproportionately burden females (Drevets et al., 2008; Riecher‐Rössler, 2017). Accordingly, rodent studies have examined the vmPFC to identify neural substrates contributing to sex‐specific vulnerability (Hurley & Carelli, 2020; van der Zee et al., 2022; Woodward et al., 2023). In vivo monitoring of vmPFC projection neurons also revealed that sex and stress history interact to shape neural activity in response to both appetitive and aversive stimuli (Wallace & Myers, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, vmPFC gray matter and functional activity are frequently altered in depression and other stress-related disorders that disproportionately burden females (Drevets et al, 2008; Riecher-Rössler, 2017). Accordingly, rodent studies have examined the vmPFC to identify neural substrates contributing to sex-specific vulnerability (Hurley & Carelli, 2020; van der Zee et al, 2022; Woodward et al, 2023). In vivo monitoring of vmPFC projection neurons also revealed that sex and stress history interact to shape neural activity in response to both appetitive and aversive stimuli (Wallace & Myers, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that there are sex differences in tolerance of stress, and in predisposition to anxiety, and depression, and that they may at least partly result from different regulation of the HPA axis [244][245]. Experimental studies demonstrated that the female rats respond with larger increases of ACTH to neurogenic stress than the male rats and suggested that during the neurogenic stress the gonadal steroids involved in the regulation of sexual behavior and reproduction may have a potential impact on the pituitary secretion of ACTH [246].…”
Section: Neurogenic Stress With Relevance To Sex Differencesmentioning
confidence: 99%
“…It is likely that one of the reasons of differences in sex-related susceptibility to stress results from functional heterogeneity of GR and MR in the brains of females and males, because higher expression of MR was found in the brain of the male mice than in the brain of female mice manifesting depressive behavior [248]. Research performed by Woodward et al (2023) on female and male mice, subjected to the UCMS procedure showed that female mice show anxiety and depressive behavior associated with FosB activation in neurons of the medial prefrontal cortex (mPFC) expressing parvalbumin after 4 weeks of exposure, while in male mice the behavioral and biochemical alterations is observed not earlier than after 8 weeks of UCMS. Furthermore, the use of patch-clamp electrophysiology allowed to demonstrate that there were time-corresponding sex-specific differences in altered neuronal excitability of the mPFC cells after 4 and 8 weeks of the exposure [245].…”
Section: Neurogenic Stress With Relevance To Sex Differencesmentioning
confidence: 99%
See 1 more Smart Citation